Dynamically vulcanized polylactic acid/natural rubber/waste rubber blends: Effect of the crosslinking agent on the morphology and tensile properties. Issue 41 (10th August 2022) - Candau, Nicolas; Albiter, Noel León; Coll, Pol Roura; Maspoch, Maria Lluïsa
Abstract: PLA/natural rubber (NR)/wastes tire rubber (GTR) were dynamically vulcanizing using dicumyl peroxide (DCP). Swelling, dissolution, and electron microscopy revealed that the unvulcanized and weekly vulcanized blends (DCP < 3 wt%) show a continuous rubber phase while the highly vulcanized blends (DCP > 3 wt%) show co‐continuous rubber/PLA phase. In the latter blends, the tensile toughness (1.3 MJ m −3 ) and the tensile‐impact strength of the neat PLA (58 kJ m −2 ) were increased of a factor 12.5 and 8.3 respectively. Moreover, the appropriate crosslinking agent content (3–3.75 wt%) in the ternary blends allowed to reach same tensile toughness, impact strength, shape recovery and shape fixity as compared to their equivalent binary PLA/NR blends. Abstract :